2009
DOI: 10.1111/j.1349-7006.2009.01153.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory (FOXP3+) T cells as target for immune therapy of cervical intraepithelial neoplasia and cervical cancer

Abstract: Regulatory (FOXP3 + ) T cells (T regs ) comprise a subpopulation of CD4I ntense research has shown that regulatory T cells (T regs ) play a fundamental role in providing peripheral tolerance against auto and foreign antigens, whereas impairment of T reg function seems to be associated with different autoimmune diseases like systemic lupus erythematodes,(1) type 1 diabetes, (2) rheumatoid arthritis (3,4) and multiple sclerosis.(5) Particularly stimulating for oncologic research was that increased frequencies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 41 publications
3
55
1
3
Order By: Relevance
“…Given the fi ndings that indicate the involvement of cells with regulatory properties, especially T reg cells, in the progression of cervical malignant lesions 3,4,23,24 , this study aimed to detect both CD25 and GITR markers in lymphocytes of cervical stroma to better understand the immune response in the microenvironment of HPV infection, which may shed light on novel therapeutic interventions against intraepithelial neoplasia and cervical cancer of viral etiology, and perhaps also make GITR a possible candidate biomarker for disease evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fi ndings that indicate the involvement of cells with regulatory properties, especially T reg cells, in the progression of cervical malignant lesions 3,4,23,24 , this study aimed to detect both CD25 and GITR markers in lymphocytes of cervical stroma to better understand the immune response in the microenvironment of HPV infection, which may shed light on novel therapeutic interventions against intraepithelial neoplasia and cervical cancer of viral etiology, and perhaps also make GITR a possible candidate biomarker for disease evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated increased frequencies and suppressive activity of T reg cells in patients with high-grade lesions and cervical cancer. In addition, compared to colorectal cancer, skin melanoma, and bronchial carcinoma, HPV-derived CIN lesions and cervical carcinomas have higher numbers of T reg cells 23,24 .…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Indeed, a strong immune response might be inefficient and succumb to an overwhelming tumor. The recruitment of T regulatory cells found in humans in many types of tumors ( [33][34][35][36] and in particular in cervical carcinoma 37 ) is an important obstacle for cancer vaccines. In a previous work, we have found that tumor infiltrating Treg numbers increased over time in TC-1 tumors, reaching almost 50% of total CD4 þ cells 25 days after tumor inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Piersma et al 31 found a significantly stronger CD8 1 T-cell tumor infiltration, a higher CD8 1 /CD4 1 T-cell ratio, and a higher CD8 1 /Tregs ratio in patients with tumors that failed to metastasize to the tumor-draining lymph node. Loddenkemper et al, 27 in a comparison study of high-grade CIN (CIN III) and cervical carcinoma with colon cancer, skin melanoma and bronchial carcinoma, revealed that HPV-derived lesions have a significantly higher number of infiltrating lymphocytes and FOXP3 1 Tregs as compared with three other common tumor types. Similar to the above studies, in our study, we observed a reversed CD4/CD8 ratio in cervical cancer.…”
Section: Comparative Numbers Of Cd4mentioning
confidence: 99%
“…25 Using an assay to determine the immune microenvironment of cervical cancer, others have shown a type II predominance. 26,27 Cervical cancer is one of the most common malignancies of married women globally and is the result of an uncontrolled persistent infection with a high-risk human papillomavirus (HPV) type, HPV16 and HPV18 in particular, which account for approximately two-thirds of these cancers. 28,29 The immune microenvironment of cervical cancer not only shares the nature of solid tumors in general, but also possesses the properties associated with its etiology.…”
Section: Introductionmentioning
confidence: 99%